How does planting structure change affect the agricultural net carbon sink? Evidence from the Jiangsu coastal economic Belt - Xiaomei Shen; Rong Yan; Mingdong Jiang (Ecological Indicators)
As one of the terrestrial ecosystems, the agroecosystem is an essential source of both greenhouse gas absorption and emission. Therefore, changes in agricultural land use significantly affect the regional net carbon sink (NCS). To further investigate this path, this paper calculated the agricultural greenhouse gas emissions and absorption status to analyze the NCS in 20 districts and counties within the Jiangsu Coastal Economic Belt (JCEB) from 2000 to 2020. On this basis, an extended Logarithmic Mean Divisia Index (LMDI) model was established to empirically decompose the driving effort of planting structure change (PSC) on NCS. We also compared the subdivision effect of PSC with its spatiotemporal characteristics and evolution patterns. Results indicate that the agricultural NCS in JCEB increased from 7.16 × 106 tC to 1.02 × 107 tC, demonstrating a state of carbon surplus that first decreased and then increased during the study period. We further proved that PSC inhibited the growth of the agricultural NCS in JCEB, while this effect shows a fluctuating decline. From a spatial perspective, the influence of the PSC on the NCS in southern regions is relatively high compared to that of northern JCEB. Specifically, the grain structural effect (GSE) and grain-cash crop structural effect (GCSE) on the agriculture NCS shift from suppression to promotion, with turning points occurring in 2011 and 2015, respectively. Moreover, the changes in the cash crop structural effect (CSE) had an ongoing dampening impact on the NCS. Based on the above research, we propose implications for using resource endowments, adjusting crop planting structure, and optimizing land use.